2015
DOI: 10.18004/rvspmi/2312-3893/2015.02(02)43-051
|View full text |Cite
|
Sign up to set email alerts
|

Adherencia al tratamiento antihipertensivo en pacientes ambulatorios de un hospital urbano

Abstract: ResumenIntroducción: la hipertensión arterial es una de las enfermedades crónicas más prevalentes en la población adulta. Su tratamiento incluye medidas higienicodietéticas y fármacos. La adherencia al tratamiento farmacológico es esencial para lograr el objetivo del control de la hipertensión arterial y minimizar las secuelas a largo plazo. Objetivos: determinar la adherencia al tratamiento antihipertensivo y factores asociados al cumplimiento terapéutico Metodología: estudio observacional, descriptivo, prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
1
1
0
7
Order By: Relevance
“…The rates of adherence vary between countries due to different types of population, study designs, and scales used to measure medication adherence [ 9 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Despite the wide variability of methods assessing medication adherence around the world, the low-moderate adherence prevalence found in our study was similar to that of persons diagnosed with hypertension in Latin American cities [ 23 , 24 , 25 , 26 , 27 , 32 ], as well as other populations from other places in the world such as Africa [ 30 , 31 ] and Asia [ 28 , 33 ]. A 2015 Spanish study using MMAS-4 showed a better adherence than our results [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of adherence vary between countries due to different types of population, study designs, and scales used to measure medication adherence [ 9 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Despite the wide variability of methods assessing medication adherence around the world, the low-moderate adherence prevalence found in our study was similar to that of persons diagnosed with hypertension in Latin American cities [ 23 , 24 , 25 , 26 , 27 , 32 ], as well as other populations from other places in the world such as Africa [ 30 , 31 ] and Asia [ 28 , 33 ]. A 2015 Spanish study using MMAS-4 showed a better adherence than our results [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Creemos que esto se podría explicar por la alta tasa de no adherencia al tratamiento, lo cual en nuestro país llega hasta valores del 59% en pacientes (27) ambulatorios . Otras investigaciones a nivel país hablan de un nivel de adherencia de solo el 39,7%, siendo factores que se asocian de forma positiva a este hecho: la edad entre 50 a 69 años, ocupación (28) activa, menor número de fármacos antihipertensivos, entre otros . Estos hallazgos resultan cruciales para la toma de decisiones en salud pública, pudiendo incluso abrir las puertas a medidas sanitarias que fortalezcan la atención primaria en salud y el manejo ambulatorio de pacientes con enfermedades crónicas controlables, como la hipertensión.…”
Section: Discussionunclassified
“…Se recomienda evaluar las causas de control inadecuado de la HTA en las USF. La adherencia al tratamiento antihipertensivo en pacientes ambulatorios de un hospital urbano del Paraguay resultó (31) sólo 39,7% .…”
Section: Discussionunclassified